Raw Starch-Digesting Glucoamylase Production of Rhizopus sp . MKU 40 Using a Metal-Ion Regulated Liquid Medium - Mizuno, Kouhei; Matsunaga, Mayumi; Morita, Hiroshi; Fujio, Yusaku (Journal of Applied Glycoscience, 1999)
In this study we attempted to control some specified metal-ion concentrations in a liquid medium and found a highly raw starch-digesting glucoamylase (RSDG) producing culture with protease-less activity, which we have called a metal-ion regulated liquid medium . Rhizopus sp. MKU 40 could not grow and produce glucoamylase (GA) in the liquid medium without metal ions (SLS medium). The addition of iron, magnesium, and zinc ions in the liquid medium was essential to growth and GA production of Rhizopus sp. MKU 40. Calcium ions also stimulated its growth and GA production. To summarize, the addition of 75 ppm calcium ions, 2 ppm iron ions, 49 ppm magnesium ions, and 0.7 ppm zinc ion to the SLS liquid medium was the best condition for producing GA and resulted in a high specific activity of GA (21.9 U/mg protein). Specific RSDG activity of the crude enzyme was 5.7 U/mg protein, and the ratio of RSDG activity to GA activity was 0.26. Since the purification was easy, the purification of GA was done in only two steps (ammonium sulfate precipitation and column chromatography on CM-Sephadex C-50) . The enzyme was purified about 4 .8-fold based on specific GA activity with an 86.0% yield based on GA activity from culture supernatant . The enzyme was proved to be homogeneous as judged by SDS-PAGE, and it has a molecular mass of about 80.4 kDa by comparison of its relative mobility on SDS-PAGE with those of standard proteins . For purified enzymes, the ratio of RSDG activity to GA activity was 0.16.